Method for improving cycle performance and power performance of lithium ion battery

By chemical etching of the foil and positive electrode gradient design, the performance problems caused by the migration of conductive agents in lithium-ion batteries are solved, and the battery cycle performance and power performance are improved.

CN119518113APending Publication Date: 2025-02-25HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411710873.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium-ion batteries, conductive agents are easily migrated to the surface of the electrode sheet, resulting in uneven distribution of conductive agents, affecting the rate performance and cycle life of the battery.

Method used

By chemically etching the foil, porous foil is made, which enhances the peeling force between the foil and the material, and adopts a positive electrode gradient design to slow down the migration rate of the conductive agent and ensures the uniform distribution of the conductive agent.

Benefits of technology

It improves the circulation and power performance of lithium-ion batteries, extends the battery life, and improves the battery's fast charging capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005155684080000011
    Figure HDA0005155684080000011
  • Figure HDA0005155684080000012
    Figure HDA0005155684080000012
  • Figure HDA0005155684080000021
    Figure HDA0005155684080000021
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a method for improving cycle performance and power performance of a lithium ion battery. The invention relates to application of a porous foil and design of a multi-gradient pore positive pole piece. The porous foil is obtained by chemical etching of an acid solution, and then is coated with a carbon layer to increase the stripping force between the foil and the material, so that the pole piece is prevented from falling off in the circulating process, and the circulating performance is improved; meanwhile, through the multi-gradient pore design of the positive electrode, the corresponding power performance can be improved while the battery capacity is considered; and the migration rate of the conductive agent to the surface of the pole piece can be effectively reduced, so that the conductive agent is uniformly distributed in the pole piece, and the rate capability of the battery is finally improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a method for improving the cycle performance and power performance of lithium ion batteries. Background Art

[0002] Lithium-ion batteries have the advantages of long cycle life, low self-discharge, and no memory effect. Since their commercialization, they have received widespread attention and application. With the widespread application of new energy vehicles, the demand for shortening the charging time of lithium-ion batteries and improving the cycle of lithium-ion batteries has become more urgent, and correspondingly, higher requirements are placed on the charging speed and life of lithium-ion batteries. However, if a high-energy density battery is produced, the coating surface density needs to be increased to increase the proportion of active materials or reduce the weight of structural parts. However, the demand for structural parts comes from the system end and basically does not change. Therefore, under the conditions of the same structural parts, the application of thick coating process is the first choice. However, with the increase in the thickness of the pole piece, the conductive agent is prone to migrate to the surface of the pole piece during the coating and drying process. As a result, the conductive agent is unevenly distributed in the pole piece, which ultimately leads to poor battery rate performance. To ensure the battery life and fast charging of lithium-ion batteries, the above problems need to be solved urgently. Summary of the invention

[0003] In response to the battery life and fast charging problems of existing lithium-ion batteries, the present invention provides a method for improving the cycle performance and power performance of lithium-ion batteries. The foil is corroded by corrosion technology to obtain a porous foil. This method enhances the peeling force between the foil and the material, thereby improving the cycle performance of the lithium-ion battery. On the other hand, the positive electrode gradient design can effectively slow down the migration rate of the conductive agent to the electrode surface, so that the conductive agent is evenly distributed in the electrode, ultimately improving the battery rate performance.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for improving the cycle performance and power performance of a lithium-ion battery, comprising the following steps:

[0005] S1, mixing the positive electrode active material LFP1, the conductive agent, the binder and NMP in a preset ratio to obtain a positive electrode coating solution 1;

[0006] S2, mixing the positive electrode active material LFP2, the conductive agent, the binder and NMP in a certain proportion to obtain a positive electrode coating solution 2;

[0007] S3, coating the dried positive electrode of the porous current collector aluminum foil by a double-layer coating method, wherein the upper layer is coated with positive electrode coating liquid 1 and the lower layer is coated with positive electrode coating liquid 2 according to a preset specific gravity;

[0008] S4, rolling and cutting the electrode sheet obtained by coating in step S3 to obtain a positive electrode sheet;

[0009] S5. Prepare finished battery cells using positive and negative electrode sheets for power and cycle testing.

[0010] Furthermore, in the aforementioned step S1, the positive electrode active material LFP1 is 9.6 kg, the conductive agent is 0.15 kg, the binder is 0.2 kg, and the NMP is 5.625 kg.

[0011] Furthermore, in the aforementioned step S2, the positive electrode active material LFP2 is 9.6 kg, the conductive agent is 0.25 kg, the binder is 0.2 kg, and the NMP is 5.625 kg.

[0012] Furthermore, in the aforementioned method for improving the cycle performance and power performance of lithium-ion batteries, the dried porous current collector aluminum foil is prepared as follows: the current collector aluminum foil is chemically etched with an oxidizing acid to obtain a porous current collector aluminum foil, a conductive carbon layer is coated on both sides of the porous current collector aluminum foil, and then dried to obtain a dried porous current collector aluminum foil.

[0013] Furthermore, in the aforementioned step S3, the dried porous current collector aluminum foil is prepared as follows: the current collector aluminum foil is chemically etched with an oxidizing acid to obtain a porous current collector aluminum foil, a conductive carbon layer is coated on both sides of the porous current collector aluminum foil, and then dried to obtain a dried porous current collector aluminum foil.

[0014] Furthermore, in the aforementioned step S3, the ratio of the upper layer of the positive electrode coating liquid 1 to the lower layer of the positive electrode coating liquid 2 is 1:1.

[0015] Furthermore, the aforementioned negative electrode sheet is prepared according to the following steps S5.1 to S5.2:

[0016] S5.1. Add graphite, a conductive agent, a binder and H2O, a negative electrode active material, into a mixing tank according to a preset ratio and stir evenly to prepare a negative electrode coating liquid;

[0017] S5.2, obtaining a negative electrode sheet by subjecting the negative electrode coating liquid to coating, rolling and slitting steps;

[0018] Furthermore, in the aforementioned step S5.1, the graphite is 9.6 kg, the conductive agent is 0.2 kg, the binder is 0.2 kg, and the deionized water is 9.23 kg.

[0019] Furthermore, in the aforementioned step S5, the positive electrode sheets and the negative electrode sheets are stacked to prepare finished battery cells for power and cycle testing, wherein there are 20 positive electrode sheets and 21 negative electrode sheets.

[0020] Furthermore, in the aforementioned step S5, the power cycle test includes a constant power test, a normal temperature cycle test, and a fast charge cycle test; specifically: constant power test: 50% SOC, -20°C, 18s and 180s discharge; normal temperature cycle test: 25°C, 0.33C charge to 100% SOC, 0.5C discharge to 0% SOC, and repeat the cycle; fast charge cycle test: 25 degrees Celsius, 0.33C charge to 15% SOC, 2C charge to 60% SOC, 1.5C charge to 90% SOC, 0.33C charge to 100% SOC, 0.5C discharge to 0% SOC, and repeat the cycle.

[0021] Compared with the prior art, the beneficial technical effects of the above technical solution of the present invention are as follows: the pole piece manufacturing process of the present invention can effectively improve the peeling force between the foil and the material area, and increase the cycle performance of the lithium-ion battery. At the same time, the use of this method to prepare the pole piece can effectively improve the distribution of the conductive agent of the positive pole piece of the lithium-ion battery, thereby improving the power performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the positive electrode porous current collector aluminum foil.

[0023] Figure 2 It is a schematic diagram of the positive electrode gradient design.

[0024] Figure 3 This is a comparison chart of the positive electrode stripping force.

[0025] Figure 4 It is a power performance comparison chart.

[0026] Figure 5 This is a comparison chart of normal temperature cycle performance.

[0027] Figure 6 This is a comparison chart of fast charging cycle performance. DETAILED DESCRIPTION

[0028] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0029] Various aspects of the invention are described herein with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the invention are not limited to those described in the accompanying drawings. It should be understood that the invention is implemented by any of the various concepts and embodiments described above, as well as the concepts and embodiments described in detail below, because the concepts and embodiments disclosed in the invention are not limited to any implementation. In addition, some aspects disclosed in the invention may be used alone or in any appropriate combination with other aspects disclosed in the invention.

[0030] The present invention provides a method for improving the cycle performance and power performance of a lithium-ion battery, comprising the following steps:

[0031] S1, mixing the positive electrode active material LFP1, the conductive agent, the binder and NMP in a preset ratio to obtain a positive electrode coating solution 1;

[0032] S2, mixing the positive electrode active material LFP2, the conductive agent, the binder and NMP in a certain proportion to obtain a positive electrode coating solution 2;

[0033] S3, coating the dried positive electrode of the porous current collector aluminum foil by a double-layer coating method, wherein the upper layer is coated with positive electrode coating liquid 1 and the lower layer is coated with positive electrode coating liquid 2 according to a preset specific gravity;

[0034] S4, rolling and cutting the electrode sheet obtained by coating in step S3 to obtain a positive electrode sheet;

[0035] S5. Prepare finished battery cells using positive and negative electrode sheets for power and cycle testing.

[0036] In the specific implementation, in step S1, the positive electrode foil is standard, refer to Figure 1 : Take a current collector aluminum foil with a thickness of 13 μm, and perform a chemical etching process with an oxidizing acid. The oxidizing acid is one of nitric acid, sulfuric acid, and hydrochloric acid, or a combination of any two or three of them. After chemical etching with the oxidizing acid, a porous current collector aluminum foil is obtained.

[0037] In step S1, the positive electrode active material LFP1, the conductive agent, the binder and NMP are added into a mixing tank in a certain proportion and stirred evenly, wherein LFP1 9.6 kg, the conductive agent 0.15 kg, the binder 0.2 kg, and NMP 5.625 kg are added to obtain a positive electrode coating liquid 1.

[0038] In step S2, the positive electrode active material LFP2, the conductive agent, the binder and NMP are added into a slurry mixing tank in a certain proportion and stirred evenly, wherein LFP2 9.6kg, the conductive agent 0.25kg, the binder 0.2kg, and NMP 5.625kg are added to obtain a positive electrode coating 2.

[0039] refer to Figure 2 In step S3, the positive electrode is coated by a double-layer coating method, and the foil used is a dried porous current collector aluminum foil, wherein the upper layer is coated with positive electrode coating liquid 1, and the lower layer is coated with positive electrode coating liquid 2, and the slurry weight ratio is 1:1.

[0040] In step S4, refer to Figure 3 The electrode sheet obtained by coating in step S3 is rolled and cut to obtain a positive electrode sheet with a size of 50*50mm for standby use.

[0041] The negative electrode sheet is prepared according to the following steps S5.1 to S5.2:

[0042] S5.1. Add the negative electrode active material graphite, conductive agent, binder and H2O into a mixing tank according to a preset ratio and stir evenly to prepare a negative electrode coating liquid; wherein 9.6 kg of graphite, 0.2 kg of conductive agent, 0.2 kg of binder and 9.23 kg of deionized water are used to prepare the negative electrode coating liquid.

[0043] S5.2. The negative electrode coating liquid is subjected to coating, rolling and slitting steps to obtain a negative electrode sheet. Specifically, the negative electrode coating liquid is subjected to coating, rolling and slitting steps to obtain a negative electrode sheet. The sheet has a size of 54*54 mm and is for standby use.

[0044] Finally, the positive electrode sheets and negative electrode sheets are stacked to prepare finished battery cells, including 20 positive electrode sheets and 21 negative electrode sheets, for power and cycle testing. ;

[0045] The implementation also includes the following power test, normal temperature cycle test, and fast charge cycle test; reference Figure 4 , Figure 5 , Figure 6 , specifically including steps S10 to S12:

[0046] Step S10: Power test conditions: constant power test, 50% SOC, -20°C, 18s and 180s discharge;

[0047] Step S11: Normal temperature cycle test: 25°C, charge at 0.33C to 100% SOC, discharge at 0.5C to 0% SOC, repeat the cycle;

[0048] Step S12: Fast charge cycle test: 25 degrees Celsius, 0.33C charge to 15% SOC, 2C charge to 60% SOC, 1.5C charge to 90% SOC, 0.33C charge to 100% SOC, 0.5C discharge to 0% SOC, repeat the cycle;.

[0049] Although the present invention has been described above with preferred embodiments, it is not intended to limit the present invention. A person skilled in the art of the present invention may make various modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A method for improving the cycle performance and power performance of a lithium-ion battery, characterized in that: The following steps are involved: S1, mixing the positive electrode active material LFP1, the conductive agent, the binder and NMP in a preset ratio to obtain a positive electrode coating solution 1; S2, mixing the positive electrode active material LFP2, the conductive agent, the binder and NMP in a certain proportion to obtain a positive electrode coating solution 2; S3, coating the dried positive electrode of the porous current collector aluminum foil by a double-layer coating method, wherein the upper layer is coated with positive electrode coating liquid 1 and the lower layer is coated with positive electrode coating liquid 2 according to a preset specific gravity; S4, rolling and cutting the electrode sheet obtained by coating in step S3 to obtain a positive electrode sheet; S5. Prepare finished battery cells using positive and negative electrode sheets for power and cycle testing.

2. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S1 , the positive electrode active material LFP1 is 9.6 kg, the conductive agent is 0.15 kg, the binder is 0.2 kg, and the NMP is 5.625 kg.

3. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S2, the positive electrode active material LFP2 is 9.6 kg, the conductive agent is 0.25 kg, the binder is 0.2 kg, and the NMP is 5.625 kg.

4. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: The dried porous current collector aluminum foil is prepared as follows: the current collector aluminum foil is chemically etched with an oxidizing acid to obtain a porous current collector aluminum foil, a conductive carbon layer is coated on both sides of the porous current collector aluminum foil, and then dried to obtain a dried porous current collector aluminum foil.

5. The method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S3, the dried porous current collector aluminum foil is prepared as follows: the current collector aluminum foil is chemically etched with an oxidizing acid to obtain a porous current collector aluminum foil, a conductive carbon layer is coated on both sides of the porous current collector aluminum foil, and then dried to obtain a dried porous current collector aluminum foil.

6. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S3, the ratio of the upper layer of positive electrode coating liquid 1 to the lower layer of positive electrode coating liquid 2 is 1:

1.

7. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: The negative electrode sheet is prepared according to the following steps S5.1 to S5.2: S5.

1. Add graphite, a conductive agent, a binder and H2O, a negative electrode active material, into a mixing tank according to a preset ratio and stir evenly to prepare a negative electrode coating liquid; S5.

2. The negative electrode coating liquid is subjected to coating, rolling and slitting steps to obtain a negative electrode sheet.

8. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 7, characterized in that: In step S5.1, the graphite is 9.6 kg, the conductive agent is 0.2 kg, the binder is 0.2 kg, and the deionized water is 9.23 kg.

9. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S5, the positive electrode sheets and the negative electrode sheets are stacked to prepare finished battery cells for power and cycle testing, wherein: There are 20 positive electrodes and 21 negative electrodes.

10. A method for improving the cycle performance and power performance of a lithium-ion battery according to claim 1, characterized in that: In step S5, the power cycle test includes constant power test, normal temperature cycle test, and fast charge cycle test; specifically: constant power test: 50% SOC, -20℃, 18s and 180s discharge; normal temperature cycle test: 25℃, 0.33C charge to 100% SOC, 0.5C discharge to 0% SOC, and repeat the cycle; fast charge cycle test: 25 degrees Celsius, 0.33C charge to 15% SOC, 2C charge to 60% SOC, 1.5C charge to 90% SOC, 0.33C charge to 100% SOC, 0.5C discharge to 0% SOC, and repeat the cycle.

Citation Information

Patent Citations

  • Method for preparing electrode plate of lithium ion battery

    CN102769122A

  • A positive electrode plate and a lithium ion battery

    CN109004171A

  • Preparation method of positive electrode piece of lithium-ion battery and positive electrode piece thereof

    CN110071292A

  • Manufacturing method of lithium-ion battery positive electrode

    CN111864185A

  • Preparation method of lithium ion battery pole piece with special structure

    CN112038580A